A COGNITIVE STYLISTIC ANALYSIS OF PINK FLOYD’S SONG LYRIC “TIME” - Sirait, Anjeli Lorena; Siburian, Jessica Br.; Sitompul, Ines Margaretha; Rangkuti, Rahmadsyah (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2024)
The objective of this paper is to describe how the content of song lyrics interacts with concepts of time, memory, and human experience and knowing how language and cognition are interrelated to create profound artistic expression in music through scheme theory, metaphor theory, and figures of speech as features of creativity and novelty in language use. The data was derived from the song entitled Time by Pink Floyd. The research method used in this study is qualitative descriptive. The result of this study is skillfully employing various figures of speech, such as metaphor, personification, and paradox, to convey the complexities of time, aging, regret, and the human experience. These literary devices engage the listener's intellect and emotions, prompting reflection on the passage of time and its impact on our lives. Furthermore, the song employs schema theory to activate the "Time that has passed" schema in listeners, encouraging them to reflect on the value of time and the importance of seizing precious moments before they slip away. The song's vivid imagery and metaphors serve as a bridge between abstract concepts and concrete experiences, making it a relatable and thought-provoking piece of art.